Complementary Use of Bioluminescence Imaging and Contrast-Enhanced Micro—Computed Tomography in an Orthotopic Brain Tumor Model. Issue 1 (1st January 2015) - Yahyanejad, Sanaz; Granton, Patrick V.; Lieuwes, Natasja G.; Gilmour, Lesley; Dubois, Ludwig; Theys, Jan; Chalmers, Anthony J.; Verhaegen, Frank; Vooijs, Marc
Small animal models are crucial to link molecular discoveries and implementation of clinically relevant therapeutics in oncology. Using these models requires noninvasive imaging techniques to monitor disease progression and therapy response. Micro–computed tomography (CT) is less studied for the in vivo monitoring of murine intracranial tumors and traditionally suffers from poor soft tissue contrast, whereas bioluminescence imaging (BLI) is known for its sensitivity but is not frequently employed for quantifying tumor volume. A widely used orthotopic glioblastoma multiforme (GBM) tumor model was applied in nude mice, and tumor growth was evaluated by BLI and contrast-enhanced microCT imaging. A strong correlation was observed between CT volume and BLI-integrated intensity (Pearson coefficient ( r ) = .85, p = .0002). Repeated contouring of contrast-enhanced microCT-delineated tumor volumes achieved an intraobserver average pairwise overlap ratio of 0.84 and an average tumor volume coefficient of variance of 0.11. MicroCT-delineated tumor size was found to correlate with tumor size obtained via histologic analysis (Pearson coefficient ( r ) = .88, p = .005). We conclude that BLI intensity can be used to derive tumor volume but that the use of both contrast-enhanced microCT and BLI provides complementary tumor growth information, which is particularly useful for modern small animal irradiation devices that make use of microCT and BLI for treatment planning, targeting, and monitoring.